"Lo Quarter": the Alghero plague cementery (1582-1583 AD) (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: Yersinia pestis; RDT for plague; 16th century Sardinia; funerary practices